Welcome to Champ Camp: An Observational Study on the Education and Preparation of Youth Athletes for a Multi-sport Games - Michael Naraine (Bowling Green State University, 2021)
Youth multi-sport events offer athletes an opportunity to prepare and train for traditional (adult) multi-sport competitions like the Olympic Games, but simultaneously raises questions as to how athletes train and prepare for the former. Thus, the purpose of this study was to uncover how youth athletes were being educated and prepared for a multi-sport games, and whether this preparation was congruent with the circumstances that athletes would encounter. To do so, the Australian Olympic Committee's "Champ Camp" pre-Games summit was observed, documenting the educational training youth athletes received prior to attending the 2018 Buenos Aires Youth Olympic Games. The findings indicate that youth athletes experienced an overload of information that focused on professionalization, and ignored social issues (e.g., sexual health) that were experienced at the Games. The findings underscore the importance of increasing socialization activities in preparing for a youth multi-sport competition.